STUDY OF DRUG THERAPY IN PATIENTS WITH GASTRITIS IN PEMATANG RAYA HEALTH CENTER, SIMALUNGUN REGENCY, APRIL - JUNE 2017 PERIOD - Beta Hanindiya; Mustaruddin (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
Drug administration therapy is aimed at improving the quality or maintaining the patient's life, there are things that cannot be expected in drug administration, namely the possibility of treatment results not being as expected. Inaccurate diagnosis makes sufferers do not get the right treatment so that their condition worsens. This research is a quantitative descriptive study, the purpose of this study was to determine the combination of drug administration in gastritis patients at the Pematang Raya Public Health Center. The data used was obtained from the medical records of Dulalowo National Health Center patients, including data on the patient's name, age, date of admission, patient complaints, and type of drug given. After the data is obtained, it is then summarized and processed in a quantitative descriptive manner. From the results of a study of the medical records of patients at the Pematang Raya Public Health Center, it was shown that 15 patients received a combination of 4 drugs, namely a combination of antacids, CTM, Ratinidin and vitamins. 6 patients received a combination of 3 drugs, namely a combination of antacids, Ratinidin and vitamins. 5 patients received a combination of 2 drugs, namely a combination of antacids and ratinidin. While 2 patients received a combination of 5 drugs namely a combination of mefenamic acid, Cotrimoxazole, Captopril, Lansoprazole and HCT.